Chiral selectors in CE: Recent developments and applications. Issue 1 (7th January 2013) - Tsioupi, Despina A.; Stefan‐vanStaden, Raluca‐Ioana; Kapnissi‐Christodoulou, Constantina P.; Rassi, Ziad El
<x xml:space="preserve">Abstract</x> This review article provides an overview of the recent advances in enantioanalysis by use of electrophoretic techniques. Due to the big number of publications in the subject mentioned above, this article is focused on chiral method developments and applications published from 2008 until 2011, and it demonstrates chiral selectors used in CE. Numerous chiral selectors have been used over the years, and these include the cyclic and the linear oligo‐ and polysaccharides, the branched polysaccharides, the polymeric and monomeric surfactants, the macrocyclic and other antibiotics, and the crown ethers. Different dual‐selector systems are also presented in this article, and the results are compared with those obtained by use of a single chiral selector. Finally, several pharmaceutical and biomedical applications based on chiral recognition are summarized.